Research and extraction of the remains of two medieval ships in Rab (In situ, 2024)
Remains of two ships were discovered, at a distance of about 4 m from each other during the archaeological inspection in the city of Rab. The remains of ship Rab 1 were laid in a northeast-southwest direction, with a length of about 7 m and a width of about 2.5 m, and on the northeast side they were under the profile of the construction trench. The remains of ship Rab 2 were found in a much worse condition, and were preserved in an area of about 3 m2. Radiocarbon analyses showed that first ship was used during the 15th century, and the second somewhat later. Extraction of the remains of the ships was carried at the end of 2022, in rather unfavorable weather conditions. However, even though rainy periods hindered work in the field, the wet conditions favored the condition of the ships, and the research campaign was brought to an end successfully.
Keywords: Rab; wodden ships; Medieval period